Flow Cytometric Evaluation of Human Neutrophil Apoptosis During Nitric Oxide Generation In Vitro: The Role of Exogenous Antioxidants - Zofia Sulowska; Ewa Majewska; Magdalena Klink; Malgorzata Banasik; Henryk Tchórzewski (Hindawi Limited, 2005)
Among numerous inflammatory mediators a nitric oxide molecule is supposed to be important in the modulation of neutrophil survival in vivo and in vitro. The effect of exogenous supply of NO donors such as SNP, SIN-1, and GEA-3162 on the course of human neutrophil apoptosis and the role of extracellular antioxidants in this process was investigated. Isolated from peripheral blood, neutrophils were cultured in the presence or absence of NO donor compounds and antioxidants for 8, 12, and 20 hours. Apoptosis of neutrophils was determined in vitro by flow cytometric analysis of cellular DNA content and Annexin V protein binding to the cell surface. Exposure of human neutrophils to GEA-3162 and SIN-1 significantly accelerates and enhances their apoptosis in vitro in a time-dependent fashion. In the presence of SNP, intensification of apoptosis has not been revealed until 12 hours after the culture. The inhibition of GEA-3162- and SIN-1-mediated neutrophil apoptosis by superoxide dismutase (SOD) but not by catalase (CAT) was observed. Our results show that SOD and CAT can protect neutrophils against NO-donors-induced apoptosis and suggest that the interaction of NO and oxygen metabolites signals may determine the destructive or protective role of NO donor compounds during apoptotic neutrophil death.